Courses
Courses for Kids
Free study material
Offline Centres
More
Store Icon
Store

How do you solve \[7h + 2h - 3 = 15\]?

seo-qna
Last updated date: 20th Jun 2024
Total views: 373.5k
Views today: 8.73k
Answer
VerifiedVerified
373.5k+ views
Hint: In the given problem we need to solve this for ‘h’. We can solve this using the transposition method. The common transposition method is to do the same thing (mathematically) to both sides of the equation, with the aim of bringing like terms together and isolating the variable (or the unknown quantity). That is we group the ‘h’ terms one side and constants on the other side of the equation.

Complete step-by-step solution:
Given, \[7h + 2h - 3 = 15\].
Adding the like terms in the left hand side of the equation,
\[9h - 3 = 15\]
We transpose ‘3’ which is present in the left hand side of the equation to the right hand side of the equation by adding ‘3’ on the right hand side of the equation.
\[9h = 15 + 3\]
\[9h = 18\]
Divide the whole equation by 9,
\[h = \dfrac{{18}}{9}\]
\[ \Rightarrow h = 2\]
This is the required answer.

Note: We can check whether the obtained solution is correct or wrong. All we need to do is substituting the value of ‘h’ in the given problem.
\[7(2) + 2(2) - 3 = 15\]
\[14 + 4 - 3 = 15\]
\[18 - 3 = 15\]
\[ \Rightarrow 15 = 15\]
Hence the obtained answer is correct.
We know that the product of two negative numbers is a positive number. Product of a negative number and a positive number gives negative number (vice versa)